AN OVERVIEW OF BIOTIC IMPACT ON SAFFRON CULTIVATION IN KASHMIR. - JOO, GH. NABI; AHMAD, SYED MUZAFFER (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2016)
Kashmir saffron a highly prized spice known all over the world for its panacea properties, is dying a slow death. . The present compilation attempts to visualize the influence of various types of biotic interferences on this golden spice and how the interference has affected the livelihood of the people directly or indirectly connected with cultivation or trade of this golden spice. Thousands of families cultivate it as a family profession for their decent livelihood. A preview of cultivated area, production and productivity for the last decade and half shows that this golden crop is dwindling at a fast rate. Further the continued impassivity and various challenges may result in the loss of this delicacy, due to a created damaged atmosphere.